Development of Hexaploid (AABBJJ) Tritipyrums with rearranged Thinopyrum distichum (Thunb.) Á Löve‐derived Genomes. Issue 6 (1st November 2014) - Marais, Francois; Simsek, Senay; Poudel, Roshan Sharma; Cookman, Davey; Somo, Mohamed
ABSTRACT: Development of durum wheat ( Triticum turgidum L.) × Thinopyrum hybrids as a new salt‐tolerant crop was first attempted in England. These hybrids (here called b‐tritipyrums) were based on the diploid grass Th. bessarabicum (Savul. & Rayss) Á Löve . Although salt tolerant, b‐tritipyrums (AABBJ b J b ) had poor agrotype, brittle rachis, and poor threshability, which impeded their continued development. In this study, we have developed alternative hexaploid hybrids (d‐tritipyrums) containing a single, rearranged J genome from Th. distichum (Thunb.) Á Löve (a segmental autotetraploid; J1 d J1 d J2 d J2 d ). Four first generation d‐tritipyrums with genomes AABBJJ were selected from segregating generations of crosses among primary and secondary durum wheat × Th. distichum amphiploids. The J genome in each appears to consist of seven rearranged Thinopyrum chromosomes, with each individual chromosome having been derived from either of the J1 d or J2 d genomes and altered through recombination with its homoeologue. A lineage with seedling salt tolerance, nonbrittle rachis, and moderately good threshability was then crossed with common wheat ( Triticum aestivum L.) × Th. distichum secondary amphiploids to broaden J‐genome variability. Despite close homoeology, the J1 d and J2 d genomes appear to be highly diverse and second‐generation hexaploids and near‐hexaploids exhibited a rich diversity of Thinopyrum ‐derived traits. Continued breeding for productivity in marginal soils can further the development of d‐tritipyrums to constitute an intermediate, well‐adapted germplasm. It will then be possible to compare it more effectively to wheat for the analysis and transfer of key physiological trait genes from the J genomes.